Plays that will be lost or about editorial aesthetic power - Wolińska, Adrianna (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The content of the article concerns the creation of aesthetic trends in recent Polish drama. The author compares the categories of power over the production of discourse, proposed by Michel Foucault, to the exercise of editorial or jury power over the publication or rewarding of texts for theater. He identifies two institutions as having the greatest influence - the magazine Dialog and the Gdyńska Nagroda Dramaturgiczna competition. The article raises the issue of texts rejected by those who evaluate them. The author wonders whether perhaps it is these texts that would not become for researchers a real landscape of different realities, when the texts selected by the institutions, are only a slice of it. To this end, she looks at the dramas created during the coronavirus pandemic, taking this event as formative, from which time the texts will become, or perhaps have already become, a vehicle for cultural memory.